Reactive Oxygen Species (ROS) in Living Cells 2018
DOI: 10.5772/intechopen.71547
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species: The Good and the Bad

Abstract: This chapter summarizes recent research on the biology of reactive oxygen species (ROS). The chapter is focused on the bimodal actions of ROS, which can be summarized as both beneficial and negative. The beneficial aspects of ROS are related to their effects on the redox state of cells and the important role that some ROS play in signaling cascade. The detrimental effects of ROS are related excess amounts of these chemical moieties, which are caused by excessive production and/or insufficient actions of endoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 44 publications
0
67
0
2
Order By: Relevance
“…Several studies have attributed oxidative stress as one of the mechanisms in which FB 1 exerts its toxicity [ 39 , 40 , 41 , 42 , 43 ]. Excessive production of reactive oxygen species (ROS) results in oxidative damage to cells and macromolecules including DNA [ 44 ]. While some studies have disputed the genotoxic potential of FB 1 [ 17 , 18 ], others have reported chromosomal aberrations and oxidative DNA damage triggered by FB 1 exposure [ 16 , 39 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have attributed oxidative stress as one of the mechanisms in which FB 1 exerts its toxicity [ 39 , 40 , 41 , 42 , 43 ]. Excessive production of reactive oxygen species (ROS) results in oxidative damage to cells and macromolecules including DNA [ 44 ]. While some studies have disputed the genotoxic potential of FB 1 [ 17 , 18 ], others have reported chromosomal aberrations and oxidative DNA damage triggered by FB 1 exposure [ 16 , 39 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cellular proliferation and apoptosis/necrosis, in addition to the immunity and allergy, are mostly dependent on the ROS balance [65]. Thus, ROS act as bifunctional reactors and exhibit both "good and bad" aspects in living cells, which might be similar in IVinfected host cells and the propagation of IV progeny [66]. These cellular events after IV infection were summarized in Fig.…”
Section: Influenza Virus (Iv)mentioning
confidence: 99%
“…Enzymatic antioxidants, such as glutathione peroxidases (GPxs) or superoxide dismutases (SODs), as well as nonenzymatic antioxidants (vitamin A, vitamin E, zinc, and selenium), are essential for maintaining adequate levels of ROS in the cell by disposing and removing excess free radicals. Any disruption in the ROS/antioxidants balance leads to a state of OS in the cell with damaging consequences [ 7 ].…”
Section: Introductionmentioning
confidence: 99%